2023
DOI: 10.1212/wnl.0000000000206826
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia and Lung Disease in Children With Spinal Muscular Atrophy Treated With Disease-Modifying Agents

Abstract: Background/Objective:Disease modifying agents (DMAs) for treatment of Spinal Muscular Atrophy (SMA) has evolved the SMA phenotype with improved survival. Ongoing oropharyngeal dysphagia and respiratory complications are reported. The extent of dysphagia and respiratory morbidity in this population, since DMAs introduction, has not been well described.Study design and Methods:A whole population study involved all children with treated SMA type 1-3 in our facility. Videofluoroscopic swallow studies ([VFSS] type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Subsequent real-life studies with type 1 SMA patients, including those using the drug in an expanded access program, further confirmed the positive effects of nusinersen on motor and respiratory function, as well as on the survival of patients with long-term illness and varying respiratory conditions. 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent real-life studies with type 1 SMA patients, including those using the drug in an expanded access program, further confirmed the positive effects of nusinersen on motor and respiratory function, as well as on the survival of patients with long-term illness and varying respiratory conditions. 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 …”
Section: Resultsmentioning
confidence: 99%
“…Subsequent real-life studies with type 1 SMA patients, including those using the drug in an expanded access program, further confirmed the positive effects of nusinersen on motor and respiratory function, as well as on the survival of patients with long-term illness and varying respiratory conditions. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The CHERISH trial was a placebo-randomized study that enrolled 126 patients with late-onset SMA aged 2 to 12 years. 41 The study demonstrated that patients who received nusinersen experienced clinically significant improvements in motor function compared to the control group.…”
Section: Regular Monitoring For Adverse Eventsmentioning
confidence: 99%
“…These studies highlight the need for formal swallowing assessments, even after the administration of disease modifying therapies 14 . Notably, lung disease, secondary to aspiration, is one of the most detrimental comorbidities in patients with SMA, and it remains a concern in patients who receive disease‐modifying therapies, as demonstrated in a study that characterized the clinical and radiological findings of a cohort of patients with SMA, although this was performed in an older cohort of patients 12 . The above mentioned post hoc analysis demonstrated that, while all sixty five subjects had pulmonary stability at baseline, defined as the absence of aspiration or aspiration pneumonia, a few of them (five) did not meet this endpoint at the completion of the study period 14 …”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Bulbar dysfunction is another recognized consequence of SMA, with resulting dysphagia and aspiration both in treated and untreated patients. [8][9][10][11] While safety and efficiency are important aspects of swallowing, available literature has primarily focused on safety [12][13][14] and less on efficiency. 15 Safe swallowing requires adequate airway protection from entry of ingested material through effective laryngeal vestibule closure, a tightly organized sequence of events required to protect the airway.…”
mentioning
confidence: 99%
“…More than half of type 1 SMA patients with a gastrostomy were six years old or younger, because of their age, these patients were diagnosed when treatments were already available. This indicates the continued high impact of bulbar involvement in the posttreatment era [ 29 ] and the implementation of standards of care in the management of swallowing. Bulbar and respiratory function need to be closely monitored [ 30 ].…”
Section: Discussionmentioning
confidence: 99%